Pivot : The Only Move that Matters is Your Next One - Blake, Jenny (U.K Portfolio Penguin, 2016)
"Jenny Blake, bestselling author of Life After College and former career development program manager at Google, shows how to move into your next career phase by leveraging what you already do well. Now, more than ever, we need to navigate career changes deftly and frequently. The average employee tenure in America is just four or five years, and even those job roles often change dramatically within that time frame.
Include Index and Notes
Keywords: Career development -- Career changes -- Vocational guidance